The Appeal of Gamification in E-Commerce: The Role of Vouchers, Coins, and Badges on Indonesian Consumer Behavior - Deviana Putri Septia Ningrum; Veni Vebriyanti; Siti Aisyah Hidayatul Hasanah; Naufal Firdaus; Yuni Zaroh; Fathor, Fathor; Hawa Gazani (Penerbit Hellow Pustaka, 2025)
The development of e-commerce in Indonesia encourages industry players to create innovative strategies to attract and retain consumers. One strategy that is widely used is gamification, namely the application of game elements such as vouchers, coins, and badges in e-commerce applications. This study aims to explore the extent to which Gamification products and coin rewards in the marketplace influence consumer purchasing decisions in Indonesia. This type of research is library research using qualitative descriptive analysis, namely by searching for data. The data in this study are secondary data, namely data from books, internet media, documents and journals and previous research that examines the appeal of gamification in E-commerce, the role of coin vouchers and badges on Indonesian consumer behavior. The results of the study indicate that gamification and coin rewards in the marketplace have a significant and positive influence on consumer behavior.